ANALISIS KEAMANAN WEBSITE SMAN 1 SUMBAWA MENGGUNAKAN METODE VULNERABILITY ASESEMENT: ANALISIS KEAMANAN WEBSITE SMAN 1 SUMBAWA MENGGUNAKAN METODE VULNERABILITY ASESEMENT - Yudi Mulyanto; Eka Haryanti; Jumirah Jumirah (Jurnal Informatika Teknologi dan Sains, 2021)
SMAN 1 Sumbawa is a school that provides information to students through a website-based information system to facilitate school administration services. Considering that the Website can be accessed widely, it is necessary to pay attention to the security of the Website. One of them is by using the Vulnerability Assessment method. The Vulnerability Assessment method is a method for conducting vulnerability testing on a website or application that has the potential to enter an attack which consists of several stages such as Network Discovering, Vulnerability Scanning, and Result Analysis. This stage aims to identify security holes on the SMAN 1 Sumbawa website. The tests that have been carried out have identified four levels of vulnerability, namely high, medium, low, and informational on the SMAN 1 Sumbawa website. The hight vulnerability level obtained is SQL Injection. The SQL Injection vulnerability makes it easy for attackers to access the entire database. The results of the tests that have been carried out show that the SMAN 1 Sumbawa Website has many vulnerabilities or Vulnerability that the SMAN 1 Sumbawa Website is still in an unsafe state.